"All these crazies": right-wing anti-authoritarian politics and the targeting of public police - Huey, Laura (Deviant behavior, 2025)
Drawing on a dataset comprised of 67 interviews with police personnel across Canada, as well as documents, videos and social media content, this paper examines five different types of "harms" perpetrated against police officers by individuals and groups espousing right-wing anti-authoritarian beliefs. The harms identified are: 1. actions intended to overwhelm and drain police, 2. cop-baiting, 3. doxing, 4. legal and pseudo-legal harassment and 5. politically motivated violence. Aside from presenting impacts on individual officers, this paper also considers some of the larger potential effects on the institution as a whole.